Adaptive depth tracking of underwater vehicles considering actuator saturation: Theory, simulation and experiment. (1st December 2022) - Zhong, Yiming; Yu, Caoyang; Wang, Rui; Liu, Chunhu; Lian, Lian
Abstract: This paper investigates underwater vehicles' saturated depth tracking problem via an adaptive fuzzy sliding mode controller (AFSMC) with an anti-saturation auxiliary compensator (ASAC). To suppress the chattering effect due to the discontinuity of the sliding mode control, a saturation function boundary layer is first applied in the AFSMC. Subsequently, a model-free fuzzy approximation system with a sliding mode surface as its input is designed for complex uncertainty compensation. Thereafter, a two-layer cascade ASAC is then attached to the controller to reject inherent actuator saturation efficiently. Based on the Lyapunov theorem and Barbalat's lemma, the stability of the entire closed-loop system is proved. Finally, the outperformance of the proposed depth tracking law is verified by numerical simulations and water tank experiments. Namely, there are improvements in tracking accuracy and energy consumption compared to the proportional integral differential algorithm. Highlights: The modeling uncertainty, actuator's saturation and dynamics are taken into consideration in the depth tracking of underwater vehicles. An adaptive fuzzy sliding mode controller with an anti-saturation auxiliary compensator and a saturation function boundary layer is successfully constructed. Numerical simulations and comparative experiments are performed and verify the outperformance of the designed controller.